2023
DOI: 10.1007/s00401-023-02571-3
|View full text |Cite|
|
Sign up to set email alerts
|

Increased mRNA expression of CDKN2A is a transcriptomic marker of clinically aggressive meningiomas

Abstract: Homozygous deletion of CDKN2A/B was recently incorporated into the World Health Organization classification for grade 3 meningiomas. While this marker is overall rare in meningiomas, its relationship to other CDKN2A alterations on a transcriptomic, epigenomic, and copy number level has not yet been determined. We therefore utilized multidimensional molecular data of 1577 meningioma samples from 6 independent cohorts enriched for clinically aggressive meningiomas to comprehensively interrogate the spectrum of C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 50 publications
(92 reference statements)
2
24
0
Order By: Relevance
“…We identified 181 records with four investigations meeting inclusion criteria (Fig. 1 ) [ 6 , 16 , 37 , 46 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…We identified 181 records with four investigations meeting inclusion criteria (Fig. 1 ) [ 6 , 16 , 37 , 46 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Any misclassification due to incorrect categorization based on molecular or epigenetic characteristics will impact the results, regardless of the statistical method used to analyze the data. However, due to specific molecular features, such as TERT gene alterations and CDKN2A/B homozygous deletions, is likely to impact only a minor fraction of our cohort [ 15 , 16 ]. In the present study, our primary objective was to demonstrate the implications of overlooking competing risks in the recurrence analysis of meningiomas.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, recent studies have shown that loss of p16 expression alone is not a reliable marker for CDKN2A/B loss in histologically WHO grade 1 meningioma. 13 , 25 More work is needed to determine whether the combination of p16 and MTAP IHC could be used as a surrogate for CDKN2A/B status in WHO grade 1 and 2 meningioma. Overall, while interrogation of the CDKN2A/B locus via CNV analysis or FISH continues to be the gold standard for grading meningiomas, these molecular analyses are often unavailable and/or costly in resource-limited neuropathology centers.…”
Section: Discussionmentioning
confidence: 99%
“…CDKN2A/B copy-number status was determined as described previously. 25 In brief, CDKN2A/B deletion status was evaluated by inspection of genome-wide copy-number variation (CNV) plots for each sample. “Heterozygous deletion” was called where the depth of CDKN2A/B deletion was comparable to the depth of single copy chromosomal losses in the same sample (eg, of chr 1p, 10, 22q, etc.).…”
Section: Methodsmentioning
confidence: 99%